1990
DOI: 10.1128/jvi.64.12.5701-5707.1990
|View full text |Cite
|
Sign up to set email alerts
|

Identification of individual human immunodeficiency virus type 1 gp120 amino acids important for CD4 receptor binding

Abstract: The binding of the CD4 receptor by the human immunodeficiency virus type 1 gpl20 exterior envelope glycoprotein is important for virus entry and cytopathic effect. To investigate the CD4-binding region of the gpl20 glycoprotein, we altered gpl20 amino acids, excluding cysteines, that are conserved among the primate immunodeficiency viruses utilizing the CD4 receptor. Changes in two hydrophobic regions (Thr-257 in conserved region 2 and Trp-427 in conserved region 4) and two hydrophilic regions (Asp-368 and Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
253
0
6

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(272 citation statements)
references
References 36 publications
13
253
0
6
Order By: Relevance
“…Given that we wished to focus here specifically on those constructs that were able to yield infectious virus, we did not examine the nonfunctional constructs further for the potential basis of their lack of infectivity. However, we do note that mutations in the C1 region near the HA1 insertion site can disrupt gp120-gp41 association (21), and point mutations in or near the location of epitope tag insertion in mutant HA4 are known to affect the efficiency of CD4 binding to gp120 (51,52,62). Mutations near the HA5 and HA6 sites may have affected gp160 processing (51), and insertion in V3 (mutants HA8 and HA9) may have disrupted interactions with coreceptor molecules on target cells (8).…”
Section: Resultsmentioning
confidence: 79%
“…Given that we wished to focus here specifically on those constructs that were able to yield infectious virus, we did not examine the nonfunctional constructs further for the potential basis of their lack of infectivity. However, we do note that mutations in the C1 region near the HA1 insertion site can disrupt gp120-gp41 association (21), and point mutations in or near the location of epitope tag insertion in mutant HA4 are known to affect the efficiency of CD4 binding to gp120 (51,52,62). Mutations near the HA5 and HA6 sites may have affected gp160 processing (51), and insertion in V3 (mutants HA8 and HA9) may have disrupted interactions with coreceptor molecules on target cells (8).…”
Section: Resultsmentioning
confidence: 79%
“…The CD4 binding site of the viral envelope protein gp120 is still not precisely defined. Whereas early studies indicated that this site was located in the fourth conserved (C4) domain of gp120 [58], mutational analysis and delineation of epitopes for anti-gp120 mAbs that block binding to CD4 have demonstrated that amino acid residues critical for CD4 binding are scattered throughout gp120 [59][60][61][62]. The current consensus view is that the CD4 binding site of gp120 is a complex folded structure in which amino acid residues from diverse regions are brought in close proximity [63].…”
Section: Hiv-1 Envelope Proteins and Phenotype Variabilitymentioning
confidence: 99%
“…The current consensus view is that the CD4 binding site of gp120 is a complex folded structure in which amino acid residues from diverse regions are brought in close proximity [63]. Amino acid residues Asp-338, Glu-340, Asp-427 and Trp-397 of gp120 are thought to be involved in direct binding to hydrophobic and positively charged amino acid residues in the V1 domain of CD4 [58][59][60]63,64].…”
Section: Hiv-1 Envelope Proteins and Phenotype Variabilitymentioning
confidence: 99%
“…Epitope mapping involving gpl20-specific MAbs and mutagenesis studies have shown that a C4 region that includes amino acids 389-407 is essential in CD4 binding (Cordonnier et al, 1989;Lasky et al, 1987;Olshevsky et al, 1990). Substitution of Trp-397 also impaired association between gp120 and gp41, suggesting that alterations in tertiary structure had occurred and implicating this residue in CD4 binding through preservation of proper conformation.…”
Section: Gp120mentioning
confidence: 99%